Merchandising activities of garment industry in Bangladesh : the case of MBM Garments Ltd - Pervin, Rezwana (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.